The Smartphone Use of Learning English Among University Students in A State University in Semarang - zakiyah zakiyah (JURNAL PENDIDIKAN, 2022)
Based on the finding and discussion above that the university students in a state university in Semarang used some applications and features of their smartphone to learn and sharpen their English ability such as hello English, speaky, youtube, spotify, and browser based on their needs. They are self-learner. They tend to cognitive needs because the five respondents used their smartphone to sharpen their English skills through features and applications on their smartphones. This is not only learn their English skills, but also they were able to gain information based on English which could support their English in the class.. The respondent 5 would look for information related to his English assignment that he doesn't know more about (smartphone functions as a supplement). While, the four other respondents who learn and sharpen their English skills deeper through applications provided by smartphones (smartphones function as a complement).